1999
DOI: 10.1002/(sici)1099-1573(199906)13:4<329::aid-ptr458>3.3.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial components of some cruciferae plants (Diplotaxis harra Forsk. and Erucaria microcarpa Boiss.)

Abstract: The total herb of Diplotaxis harra Forsk. on treatment with myrosinase produces isopropyl isothiocyanate and 3- butenyl isothiocyanate in addition to (the non-volatile) 2-hydroxy-3-butenyl isothiocyanate which could be obtained as 5-vinyl-2-oxazolidinethione (goitrin) and methyl 4-isothiocyanatobutyrate (Erypestrin). On treating Erucaria microcarpa Boiss, herb with myrosinase, it produces isopropyl isothiocyanate, butyl isothiocyanate and benzyl isothiocyanate in addition to the non-volatile 8-methylsulphinylo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 0 publications
0
13
0
1
Order By: Relevance
“…The thioglucosidase hydrolysed fraction was prepared according to (William et al ., ; Hashem and Wahba, ) as follows: the frozen broccoli florets were sliced (500.0 g), homogenized in a mixer with 2500 mL water, after the addition of previously prepared thioglucosidase enzyme (Hashem and Saleh, ) and then left overnight. The homogenate was centrifuged at 8000 rpm for 5 min.…”
Section: Methodsmentioning
confidence: 99%
“…The thioglucosidase hydrolysed fraction was prepared according to (William et al ., ; Hashem and Wahba, ) as follows: the frozen broccoli florets were sliced (500.0 g), homogenized in a mixer with 2500 mL water, after the addition of previously prepared thioglucosidase enzyme (Hashem and Saleh, ) and then left overnight. The homogenate was centrifuged at 8000 rpm for 5 min.…”
Section: Methodsmentioning
confidence: 99%
“…In 1995, Brabban and Edwards reported that The antibacterial properties of isothiocyanates only the hydrolysis products of the glucosinolate sinigrin displayed an effect upon the growth of micro-organisms (Brabban & Edwards, 1995). Several years later, the volatile ITC components of two Brassicaceae plant extracts were identified for their activity against yeasts, bacteria and fungi (Hashem & Saleh, 1999). There is now ample evidence for the antimicrobial properties of ITCs (Aires et al, 2009a, b), but most reports of the suppression of bacterial growth by ITCs are still limited to MIC determination.…”
Section: Mic Against Various Pathogensmentioning
confidence: 99%
“…No entanto, os extratos avaliados neste estudo mostraram-se ativos contra cepas Gram positivas e Gram negativas. Os ĂĄcidos graxos presentes, principalmente, nos extratos lipofĂ­licos podem ser os responsĂĄveis pela atividade antimicrobiana encontrada nas plantas desse estudo (Hashem;Saleh, 1999;Nazif, 2002). Foram identifi cados oito ĂĄcidos graxos diferentes nos extratos de S. oleracea e M. vinifera, como pode ser visto na Tabela 3.…”
Section: Discussionunclassified